PENGEMBANGAN MEDIA PEMBELAJARAN APRON ORGAN PADA MATA PELAJARAN IPAS DI MIN 2 KOTA PALANGKARAYA: Media Pembelajaran, Apron Organ, IPAS - Diah, Diah ayu prameswari; Prameswari, Diah ayu (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
Learning media development serves as a means to facilitate understanding among students, especially in the context of academic activities. This research uses R&D methodology, which is a type of development research. The development model used is the 4-D model (Define, Design, Development, Disseminate), with data collection techniques in the form of interviews, observations, documentation, and questionnaires. The results of this study indicate that (1) product development at the Define stage, researchers analyzed the needs, materials, and characteristics of students; (2) The feasibility of organ apron learning media is determined from the results of material expert validation in the final stage which obtained 93.75% with the criteria “Very Feasible”, while the results of media expert validation in the final stage obtained a feasibility percentage of 94.04% with the criteria “Very Feasible”; (3) The teacher's response to the organ apron media scored 96.87%, while the trial with 25 students scored 90.65% including in the “Very Good” category. Thus, it can be stated that students give positive responses to the organ apron learning media.